2021
DOI: 10.3390/microorganisms9050898
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiome of the Reef Macroalga Sargassum ilicifolium in Singapore

Abstract: The large canopy-forming macroalga, Sargassum ilicifolium, provides shelter and food for numerous coral reef species, but it can also be detrimental at high abundances where it outcompetes other benthic organisms for light and space. Here, we investigate the microbial communities associated with S. ilicifolium in Singapore, where it is an abundant and important member of coral reef communities. We collected eight complete S. ilicifolium thalli from eight island locations along an approximate 14 km east-to-west… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 75 publications
2
5
0
Order By: Relevance
“…Consistent with other work examining microbial community structure in a variety of host taxa, we show that microbial community structure does exist around the Malay Peninsula [39, 40, 54, 55, 78, 79], and this structure is driven primarily by plant part sampled, location sampled, and host identity. It is likely that these differences are driven by local environmental conditions, with locations closer together tending to have more similar environmental conditions in comparison to those that are more geographical distant.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with other work examining microbial community structure in a variety of host taxa, we show that microbial community structure does exist around the Malay Peninsula [39, 40, 54, 55, 78, 79], and this structure is driven primarily by plant part sampled, location sampled, and host identity. It is likely that these differences are driven by local environmental conditions, with locations closer together tending to have more similar environmental conditions in comparison to those that are more geographical distant.…”
Section: Discussionsupporting
confidence: 89%
“…This matches well with previous studies on the 2017) that showed that the phylum Proteobacteria or specifically Alphaproteobacteria and Gammaproteobacteria were among the most abundant classes of bacteria. These observations were also reported for the benthic Sargassum muticum (Serebryakova et al, 2018) and Sargassum ilicifolium (Oh et al, 2021). The high abundances of Rhodobacteraceae, Pseudomonadaceae and Vibrionaceae were likely related to the high release of dissolved organic matter (DOM) by holopelagic Sargassum in open waters (Powers et al, 2019;Shank et al, 2010a;Shank et al, 2010b), which stimulates the proliferation of DOM-degrading bacteria in these families of Proteobacteria (Buchan et al, 2014;Hervé et al, 2021).…”
Section: Characterization Of Holopelagic Sargassum Microbial Communitiessupporting
confidence: 57%
“…Macroalgal biomass recycling is mainly mediated by colonizing epiphytic bacteria that form dense biofilms comprising 10 3 -10 9 cells cm −2 (Martin et al, 2014;Lage and Graça, 2016). Alphaproteobacteria (e.g., Rhodobacterales and Sphingomonadales), Gammaproteobacteria (e.g., Alteromonadales, Pseudomonadales, Vibrionales), Bacteroidetes (e.g., Cytophagales and Flavobacteriales), Firmicutes (e.g., Bacillales), Actinobacteria (e.g., Actinomycetales) or Planctomycetes (e.g., Planctomycetales) are the major components of these communities (Hollants et al, 2013;Martin et al, 2014;Lage and Graça, 2016;Oh et al, 2021).…”
Section: Marine Quorum Sensing-based Communications Occur In Dense Ba...mentioning
confidence: 99%
“…Actinobacteria (Gram-positive) are ubiquitous in the ocean realm (Giovannoni and Stingl, 2005) and can reach high abundance in deep-sea sediments (Zinger et al, 2011;Chen et al, 2016), marine aggregates (Grossart et al, 2004) and macroalgae (Oh et al, 2021). Although their metabolism and roles are largely unknown, these bacteria possess various extracellular hydrolytic enzymes that are able to degrade recalcitrant OM (Lam, 2006;Chen et al, 2016).…”
Section: Actinobacteriamentioning
confidence: 99%
See 1 more Smart Citation